2013
DOI: 10.1038/onc.2013.354
|View full text |Cite
|
Sign up to set email alerts
|

Ebp1 activates podoplanin expression and contributes to oral tumorigenesis

Abstract: Podoplanin is highly expressed in human cancers. However, mechanisms regulating podoplanin expression remain elusive. Here we show that podoplanin promotes tumorigenesis of oral squamous cell carcinoma (OSCC) and precancerous cells both in vitro and in vivo, and the ErbB3-binding protein-1 (Ebp1) can be activated in oral tumorigenesis and can serve as a transcriptional activator to drive podoplanin expression in the malignant progression. Most of the OSCC cell lines have no detectable podoplanin protein in low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 33 publications
5
44
0
Order By: Relevance
“…An intriguing observation of these studies was that PDPN not only promoted cell migration and invasiveness, but also behaved as an oncogenic protein by inducing a full tumorigenic and metastatic phenotype [17] . These data were confirmed by knockdown experiments in which downregulation of PDPN in human oral SCC cell lines drastically reduced tumor formation in nude mice [18,19] . An explanation for this behavior has come recently from proteomic profiling studies in which upregulation and downregulation of pro-oncogenic and tumor suppressor proteins, respectively, were observed upon PDPN expression in MDCK cells [19] .…”
supporting
confidence: 68%
“…An intriguing observation of these studies was that PDPN not only promoted cell migration and invasiveness, but also behaved as an oncogenic protein by inducing a full tumorigenic and metastatic phenotype [17] . These data were confirmed by knockdown experiments in which downregulation of PDPN in human oral SCC cell lines drastically reduced tumor formation in nude mice [18,19] . An explanation for this behavior has come recently from proteomic profiling studies in which upregulation and downregulation of pro-oncogenic and tumor suppressor proteins, respectively, were observed upon PDPN expression in MDCK cells [19] .…”
supporting
confidence: 68%
“…Cell transfection was performed as described previously 10, 29, 30. In brief, transfection experiments were performed by using Opti-MEM medium and Lipofectamine 3000 (Invitrogen) for DNA oligonucleotides or Lipofectamine RNAiMAX (Invitrogen) for RNA oligonucleotides according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability and IC 50 were determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT, Life Technologies) assay as performed previously,10, 29, 30 and IC 50 was defined as the drug concentration that was required for 50% inhibition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent report by Mei et al (2014) suggests that the cell density is another mechanism for transcriptional regulation of podoplanin. These authors have shown that podoplanin promotes tumorigenesis in oral squamous cell carcinomas, and that this process is mediated by transcriptional up-regulation of podoplanin due to the nuclear import of ErbB3-binding protein 1 (Ebp1) under conditions of high cell density.…”
Section: Transcriptional Regulationmentioning
confidence: 99%